2018
DOI: 10.1007/s11606-018-4348-3
|View full text |Cite
|
Sign up to set email alerts
|

So Tired: Predictive Utility of Baseline Sleep Screening in a Longitudinal Observational Survey Cohort of First-Year Residents

Abstract: During PGY-1 training, residents experience worsening sleep duration, quality of sleep, and daytime sleepiness. Residents with baseline impaired sleep tend to remain impaired. Moreover, many residents with baseline normal sleep experience sleep deterioration over time. Sleep screening at residency orientation may identify some, but not all, residents who will experience sleep impairment during training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…Sleep impairment is highly prevalent among residents. [ 14 ] Prior studies have demonstrated that sleeping impairment decreased concentration and increased burnout. [ 15 , 16 ] However, in contrast to previous research, our study did not find an association between sleep time with burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep impairment is highly prevalent among residents. [ 14 ] Prior studies have demonstrated that sleeping impairment decreased concentration and increased burnout. [ 15 , 16 ] However, in contrast to previous research, our study did not find an association between sleep time with burnout.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Zebrowski et al reported that a decrease in the mean daily sleep duration led to poor sleep quality and increased daytime somnolence. 27 Thus, it could be suggested that sleep duration, daytime somnolence and sleep quality are correlated and could trigger one another.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the negative impacts on medical students, poor sleep quality of medical students may have implications for patient safety and the overall quality of health care. Sleep deprivation seriously endangers safety of physicians, trainees and the patients (42). Also, research suggests that physicians practicing healthier lifestyles in their personal life are generally more prone to the counselling of patients about preventive interventions (43).…”
Section: Discussionmentioning
confidence: 99%